Speech aggression in a epistolary text by Grygori Guseinov (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
Modern stage of linguistic progress is recognized by its increased focusing on the studies of speech aggression. Specialists in psychology, sociology, and politology take specific interest in the analysis of aggression. Linguists haves started studying aggression as a phenomenon of linguistic communication since latter half of the twentieth century. Topicality of the speech aggression investigation results from the increase in social aggression being observed in the community. Category of aggression is scantily studied problem in the context of modern linguistics; thus, objective of the paper is to determine speech aggression in terms of current Ukrainian language with the help of epistolary materials. A novel in diaries and letters “Back to Portland” by Grygori Guseinov is taken for the analysis. To achieve the objective, following problems should be solved: aggression in linguistic dictionaries; and lexical and semantical of words representing the category of speech aggression. Category of aggression holds a special place in the novel by Grygori Guseinov. Thus, his works are very important for the studies. A problem of aggression is a part of emotional experience of the writer and his internality. Hence, it is possible to consider a state of mean-spiritedness, unkindness, and aggression as lexis of a word aggression representing emotional state. Originality, novelty, and individual style of the writer are manifested in his unique mystification basing upon his fabulated chronicles. As an integral component of human consciousness, language records elements of the aggression category within definitions of defining dictionaries. Analysis of lexis of a category of aggression makes it possible to say that the majority of the lexis emotionally coloured and represented with the help of various lexical layers. In terms of factual selection of materials, the category of speech aggression is explained by means of different lexemes, i.e. aggression words expressed with the help of nouns, verbs, adjectives; moreover, lexical and semantical groups have been singled out. Determination of groups of speech aggression is an important part of the studies; it involves further studies of the lexis of semantics of aggression. Future studies will concern comparative analysis of lexical and semantical structure of the category of speech aggression.
Keywords: aggression; speech aggression; definition of forms of speech aggression expression